Micellar liquid chromatography for the determination of some less prescribed benzodiazepines - Subhra H.; Devasish B.; Josep E.-R.; Abhilasha D. (My University, 2025)
A simple chromatographic procedure is reported for the determination of some less prescribed but equally important benzodiazepines (Clotiazepam, clozapine and pinazepam) in serum. The optimization studies have been made in CN, C18 and C8 columns, using mobile phase containing sodium dodecyl sulphate (SDS) modified with either propanol, butanol or pentanol. The method proposed for the determination of the three benzodiazepines using a mobile phase of 0.13 M SDS, 2.4% pentanol-0.01 M phosphate buffer- 0.1% triethylamine (pH 7) at 25 °C and UV detection (240 nm) in a C8 column. The serum samples was injected directly, without any pretreatment, eluted in less than 8 min, in accordance to their relative polarities, as indicated by their octanol-water partition coefficients. The limits of detection (ng/mL) was in the 1.6 to 5.6 and 7 to 87 range, for aqueous and serum samples, respectively. Repeatability and intermediate precision was tested for three different concentrations of the drugs, resulting in the 0.1 to 2 range. The results obtained here for the separation of the three benzodiazepines in serum were also counter checked at Department of Bio-analytical Chemistry, Universitat Jaume I, Castelló, Spain.